ChemInform Abstract: Applications of Thiyl Radical Cyclizations for the Synthesis of Thiosugars. Issue 25 (3rd June 2013) - Malone, Aoife; Scanlan, Eoin M.
Abstract The first examples of thiyl radical cyclization applied to thiosugar synthesis are given.